PC technician street smarts : a real world guide to CompTIA A+ skills - Pyles, James (Serious skills., 2009)
"The Street Smarts series is designed to help current or aspiring IT professionals put their certification to work for them. Full of practical, real world scenarios, each book features actual tasks from the field and then offers step-by-step exercises that teach the skills necessary to complete those tasks. Broken down into the various aspects of a PC technician's job, this book provides you with step-by-step guidance for performing some of the most common and some of the most daunting tasks PC technicians face. Whether you're looking to break into the field of PC technicians, are pursuing your A+ certification, or are seeking some unique guidance to performing real-world tasks, this resource is essential"--Resource description page.